Aplikasi metode Morphological Chart pada perancangan Robot Belajar Baca (ROBOCA) untuk anak usia dini - Bertha Bintari Wahyujati (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
Children are more interested in learning if these activities are carried out while playing. So in learning for early childhood children need to learn about media while playing. On the other hand, children are introduced to technology even though it is a simple technology. Play involves creativity, an independent and fun activity, and creates curiosity to explore more. This learning to read robot uses an application RFID reader, which is operated by arranging letter cards as a word, then the reading robot will evaluate whether the word is correct, and is marked by the sound of the MP3 player. The method used to design the embodiment of the form and concept of the system for this reading robot is a morphological chart. Morphological charts allow the combination of parameters with choices as alternative concepts. The alternative concept is then selected by rating the achievement of the expected performance specifications.